Mating patterns and pollen dispersal in a heterodichogamous tree, Juglans mandshurica (Juglandaceae) - Bai, Wei-Ning (The New phytologist, 2007)
Mating patterns in heterodichogamous species are generally considered to be disassortative between flowering morphs, but this hypothesis has hitherto not been vigorously tested. Here, mating patterns and pollen dispersal were studied in Juglans mandshurica, a heterodichogamous wind-pollinated species that is widely distributed in northern and north-eastern China. Paternity analyses carried out on 11 microsatellite loci were used to estimate morph-specific rates of outcrossing and disassortative mating. Pollen dispersal and genetic structure were also investigated in the population under study. The mating pattern of J. mandshurica was highly outcrossing and disassortative. Pairwise values of intramorph relatedness were much higher than those of intermorph relatedness, and a low level of biparental inbreeding was detected. There was no significant difference in outcrossing and disassortative mating rates between the two morphs. The effective pollen dispersal distribution showed an excess of near-neighbor matings, and most offspring of individual trees were sired by one or two nearby trees. These results corroborate the previous suggestion that mating in heterodichogamous plant species is mainly disassortative between morphs, which not only prevents selfing but also effectively reduces intramorph inbreeding